â€œBadanâ€, Pelestarian Tradisi Bulan Syawal pada Masyarakat Muslim Kembangarum Kota Salatiga - Adang Kuswaya (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
This article seeks to uncover the reason culture on Muslim society Kembangarum Salatiga in the Badan tradition. It also intends to reveal the meaning of the tradition for today's society. This qualitative study uses literature review andfinds that the tradition is one of the expression of religious communities, as a manifestation of gratitude to God, concern for nature, and cohesion and communality among the public. In addition to the cultural meanings, Badan tradition also has economic and socio- cultural significance for local governments and communities.